Real-time integration of optical coherence tomography thickness map overlays for enhanced visualization in epiretinal membrane surgery: a pilot study - Turgut, Ferhat; Ueda, Keisuke; Saad, Amr; Spitznagel, Tahm; von Felten, Luca; Matsumoto, Takashi; Santos, Rui; de Smet, Marc D.; Nagy, Zoltán Zsolt; Becker, Matthias D.; Somfai, Gábor Márk (Bioengineering, 2025)
(1) Background: The process of epiretinal membrane peeling (MP) requires precise intraoperative visualization to achieve optimal surgical outcomes. This study investigates the integration of preoperative Optical Coherence Tomography (OCT) images into real-time surgical video feeds, providing a dynamic overlay that enhances the decision-making process during surgery. (2) Methods: Five MP surgeries were analyzed, where preoperative OCT images were first manually aligned with the initial frame of the surgical video by selecting five pairs of corresponding points. A homography transformation was then computed to overlay the OCT onto that first frame. Subsequently, for consecutive frames, feature point extraction (the Shi-Tomasi method) and optical flow computation (the Lucas-Kanade algorithm) were used to calculate frame-by-frame transformations, which were applied to the OCT image to maintain alignment in near real time. (3) Results: The method achieved a 92.7% success rate in optical flow detection and maintained an average processing speed of 7.56 frames per second (FPS), demonstrating the feasibility of near real-time application. (4) Conclusions: The developed approach facilitates enhanced intraoperative visualization, providing surgeons with easier retinal structure identification which results in more comprehensive data-driven decisions. By improving surgical precision while potentially reducing complications, this technique benefits both surgeons and patients. Furthermore, the integration of OCT overlays holds promise for advancing robot-assisted surgery and surgical training protocols. This pilot study establishes the feasibility of real-time OCT integration in MP and opens avenues for broader applications in vitreoretinal procedures.
Online veröffentlicht: 10. März 2025
Gesehen am 05.11.2025